Association between the central sensitization inventory score and health-related quality of life in community-dwelling middle-aged and older adults - Naoki Segi; Hiroaki Nakashima; Ryotaro Oishi; Sadayuki Ito; Jun Ouchida; Ippei Yamauchi; Yasuhiro Nagatani; Taisuke Seki; Yasuhiko Takegami; Shinya Ishizuka; Yukiharu Hasegawa; Shiro Imagama (PLoS ONE, 2025)
Background Central sensitization is an important factor associated with impaired health-related quality of life in patients with musculoskeletal disorders and community-dwelling older adults. However, health-related quality-of-life domains strongly associated with central sensitization in the general population remain unclear. This study aimed to examine the association between the Central Sensitization Inventory Part A scores and health-related quality of life using community health checkup data. Methods A total of 419 middle-aged and older adults (mean age, 64.4 ± 11.2 years; 59.4% female) were included. Participants completed a questionnaire survey on pain, including visual analogue scales (VASs) for lower-back and knee pain, and the Central Sensitization Inventory Part A. Additionally, participants completed the Short-Form 36-Item Health Survey, and three component-summary scores and eight subscales were calculated. Additionally, participants completed the 5-level EuroQol 5 dimensions, and health-state utility values were calculated. The correlation between the Central Sensitization Inventory Part A scores and these health-related quality-of-life measures was investigated. Results Central Sensitization Inventory Part A score ≥40 was observed in 2.6% participants. Significant moderate negative correlations were observed between the Central Sensitization Inventory Part A scores and EuroQol 5 dimensions health-state utility values ( r = −0.631, P < 0.001), Short-Form 36 mental-component summary ( r = −0.550, P < 0.001), body pain ( r = −0.556, P < 0.001), general health ( r = −0.556, P < 0.001), vitality ( r = −0.610, P < 0.001), and mental health ( r = −0.556, P < 0.001). Similar results were obtained for participants with Central Sensitization Inventory Part A scores <30. Conclusions In community-dwelling middle-aged and older adults, Central Sensitization Inventory Part A scores were negatively correlated with health-related quality-of-life scores, even in participants with Central Sensitization Inventory Part A scores <30.